Negotiating the North Meeting-Places in the Middle Ages in the North Sea Zone - Semple, Sarah (Taylor & Francis, 2020)
This book brings together the cumulative results of a three-year project focused on the assemblies and administrative systems of Scandinavia, Britain, and the North Atlantic islands in the 1st and 2nd millennia AD. In this volume we integrate a wide range of historical, cartographic, archaeological, field-based, and onomastic data pertaining to early medieval and medieval administrative practices, geographies, and places of assembly in Norway, Sweden, Denmark, Iceland, the Faroe Islands, Scotland, and eastern England. This transnational perspective has enabled a new understanding of the development of power structures in early medieval northern Europe and the maturation of these systems in later centuries under royal control. In a series of richly illustrated chapters, we explore the emergence and development of mechanisms for consensus. We begin with a historiographical exploration of assembly research that sets the intellectual agenda for the chapters that follow. We then examine the emergence and development of the thing in Scandinavia and its export to the lands colonised by the Norse. We consider more broadly how assembly practices may have developed at a local level, yet played a significant role in the consolidation, and at times regulation, of elite power structures. Presenting a fresh perspective on the agency and power of the thing and cognate types of local and regional assembly, this interdisciplinary volume provides an invaluable, in-depth insight into the people, places, laws, and consensual structures that shaped the early medieval and medieval kingdoms of northern Europe.